SARS-CoV-2 Spike Antagonizes Innate Antiviral Immunity by Targeting Interferon Regulatory Factor 3 - Freitas, Raul S.; Crum, Tyler F.; Parvatiyar, Kislay (Frontiers in Cellular and Infection Microbiology, 2022)
Corona virus disease 2019 (COVID-19) pathogenesis is intimately linked to the severe acute respiratory syndrome corona virus 2 (SARS-CoV-2) and disease severity has been associated with compromised induction of type I interferon (IFN-I) cytokines which coordinate the innate immune response to virus infections. Here we identified the SARS-CoV-2 encoded protein, Spike, as an inhibitor of IFN-I that antagonizes viral RNA pattern recognition receptor RIG-I signaling. Ectopic expression of SARS-CoV-2 Spike blocked RIG-I mediated activation of IFNβ and downstream induction of interferon stimulated genes. Consequently, SARS-CoV-2 Spike expressing cells harbored increased RNA viral burden compared to control cells. Co-immunoprecipitation experiments revealed SARS-CoV-2 Spike associated with interferon regulatory factor 3 (IRF3), a key transcription factor that governs IFN-I activation. Co-expression analysis via immunoassays further indicated Spike specifically suppressed IRF3 expression as NF-κB and STAT1 transcription factor levels remained intact. Further biochemical experiments uncovered SARS-CoV-2 Spike potentiated proteasomal degradation of IRF3, implicating a novel mechanism by which SARS-CoV-2 evades the host innate antiviral immune response to facilitate COVID-19 pathogenesis.